HONORARY CITIZEN OF FRANCE OR ENGLISH VOLTAIRE (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article is about an honorary citizen of France,an English Voltaire,an American revolutionary,the author of the revolutionary book ‘Common Sense’, a defender of human rights,one of the fathers of American Independence,a person who actively fought against slavery.